Holographic meridian scraping on patient with essential hypertension of phlegm-blood stasis type: A case report of treatment and nursing experience (全息经络刮痧疗法干预痰瘀互结型原发性高血压1例效果观察及护理体会) - ZHANG Man (张曼); DONG Chunfang (董春芳); ZHANG Ruoyin (张若荫); XUE Li (薛丽); Deng Yulong (邓玉龙) (中西医结合护理)
This paper reviewed the effect of holographic meridian scraping therapy on control of blood pressure and its accompanying symptoms in a patient with essential hypertension of phlegm-blood stasis type, and nursing experience during the treatment was summarized. The holographic acupoints of head, neck, shoulder and back were selected for a course of holographic meridian scraping combined with meridian acupoints. The results showed that the symptoms of dizziness, headache and insomnia were significantly improved, and the TCM syndrome score decreased and symptoms of cervical pain were relieved to a great extent. It shows that holographic meridian scraping therapy has a significant intervention effect on Phlegm and blood stasis type hypertension. It can dredge the meridians, promote blood circulation and remove blood stasis, strengthen the spleen and dry dampness, control the blood pressure level and reduce clinical symptoms, which has positive clinical significance. (本文回顾1例以辨证为基础的全息经络刮痧疗法干预痰瘀互结型原发性高血压患者血压及其伴随症状的案例, 总结相关护理经验。选取头、颈、肩、背部的全息穴区结合经络穴位对1例痰瘀互结型原发性高血压患者进行1个疗程的全息经络刮痧。患者头晕、头痛、失眠的症状较刮痧之前明显好转, 中医证候评分下降, 颈椎疼症状有效缓解。全息经络刮痧疗法对痰瘀互结型高血压的干预效果明显, 能够疏通经络、活血化瘀、健脾燥湿, 控制血压水平, 减轻临床症状, 具有积极的临床意义。)